2013
DOI: 10.1179/1743284712y.0000000129
|View full text |Cite
|
Sign up to set email alerts
|

Laser arc hybrid weld microstructure in nickel based IN738 superalloy

Abstract: A study of the microstructural characteristics of laser arc hybrid welded nickel based IN738 superalloy was performed. Laser arc hybrid welding produced a desirable weld profile in the alloy, similar to what is usually obtained during laser beam welding, and no cracking occurred exclusively in the fusion zone. Elemental partitioning pattern in the fusion zone was studied by electron probe microanalysis and calculating the volume fraction of the weld metal that resulted from the consumption of the filler wire. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…TEM analysis of similar particles in the material that was laser arc hybrid welded with IN718 wire showed that the particles are MC type carbides with a lattice parameter of y0?446 nm. 15 SEM also revealed that some of the carbides formed a lamellae eutectic type structure with the c matrix along the interdendritic regions (Fig. 5).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…TEM analysis of similar particles in the material that was laser arc hybrid welded with IN718 wire showed that the particles are MC type carbides with a lattice parameter of y0?446 nm. 15 SEM also revealed that some of the carbides formed a lamellae eutectic type structure with the c matrix along the interdendritic regions (Fig. 5).…”
Section: Resultsmentioning
confidence: 95%
“…9,13,14 This has made the technology attractive and promising for the joining of several materials, especially those that are difficult to weld. In a recent microstructural study of laser arc hybrid welded nickelbase IN738 superalloy by the present authors, 15 the technology was found to be usable for the joining of nickel-base superalloys, producing a desirable weld bead shape and appearance. Unfortunately, the study showed that the material is highly susceptible to HAZ intergranular liquation cracking during laser arc hybrid welding.…”
Section: Introductionmentioning
confidence: 92%
“…It is known that, during laser-arc hybrid welding, vaporization takes place from both the base alloy and the hot welding wire, such that more metal vapor is available in the keyhole [5]. The effect of this synergy, for the same laser power, is usually observed in the form of increased keyhole penetration during laser-arc hybrid welding compared to laser only [27]. Figure 3 is a schematic representation of a section along the weld bead during laser-arc hybrid welding, illustrating the contributions of the laser beam and the arc to keyhole behavior and the formation of macro-size pores in the weld metal.…”
Section: Resultsmentioning
confidence: 95%
“…They established the relationship between porosity, weld depth, welding velocity, and defocus through a large number of experiments. O T Ola et al [5] used the laser-TIG hybrid process to weld Inconel 738 superalloy plates with a thickness of 10 mm, and obtained high-quality welded joints with good textures and no cracks. Wang J et al [6] used pulse laser welding technology to complete c-276 superalloy sheet welding with a thickness of only 0.381mm and analyzed the weld texture, element segregation, and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%